DESIGNING THE SHORT FILM “KACAU, AKU RINDU” AS A REPRESENTATION OF THE MENTAL CRISIS OF FINAL SEMESTER STUDENTS - Teraguna, Jofran Calfin; Widagdo, Pratama Bayu (LPPM Univ. Ibn Khaldun Bogor, 2025)
The short film Kacau, Aku Rindu depicts the mental struggle experienced by students in their final semester, who are often hampered by anxiety related to academic tasks and homesickness. These emotions can interfere with their concentration in completing their final project, which is the culmination of their academic journey. Based on real-life experiences, the film emphasizes the importance of social support from peers in helping students cope with emotional distress and maintain focus on their studies. With a strong narrative and immersive visuals, the film invites viewers to be more sensitive to mental health issues among college students and understand the importance of social support in dealing with them. The thoughtful production, both technically and narratively, aims to raise awareness about the importance of mental health on campus and open up space for further discussion on the issue.